Impact of vehicle speeds and changes in mean speeds on per vehicle-kilometer traffic accident rates in Japan - Masayoshi Tanishita (IATSS Research, 2017)
Speed and speed variation are widely believed to be key issues in the understanding of traffic accidents. However, there has not been a substantial amount of research that focuses on the interaction between the mean speed and the change in the mean speeds. In this paper we use a five-minute continuous monitoring data of the mean speed on an expressway in Japan. Applying a two dimensional additive Poisson model, we show that not only mean speeds but also changes in mean speeds affect per vehicle-kilometer traffic accident rates. The highest probability of an accident occurs when speed reduces from 110 to 85 km/h. Another area of high accident probability occurs when the average speed increases from 65 to 90 km/h. In addition, we found that accident rates are higher when there is sunny weather, rather than when it is cloudy.